Dynamic Characteristics and Anti-slip Grasping of Two-Finger Translational Manipulator - Liu, Wei; Cheng, Jin; Wan, Ping; Jing, Cheng; Ma, Yongheng; Chen, Keshiting (Frontiers in Neurorobotics, 2021)
Aiming at the problem of deformation and slip of disc-shaped rubber gasket in the process of grasping, a two-finger translational manipulator based on ABB1410 robot is designed. The kinematics model of the two-finger translational manipulator is established, and the geometric relationship between the motor angle and grasp position is obtained. Based on the two-dimensional force sensor, the dynamic characteristics of the two-finger translational manipulator were studied, and the relationship between the grasping force and the deformation and slip of the disc-shaped rubber gasket was obtained. A prototype of two-finger translational manipulator is developed. The experimental results show that when the grasping force is 5 N, small deformation and stable grasping can be achieved. The grasping and handling process of disk-shaped rubber gasket is designed based on Robot Studio software, and the verification experiments were carried out. The experimental results show that the system can achieve the small deformation and stable grasping of flexible objects, which is consistent with the simulation results. The research can provide theoretical and experimental basis for the design of automation system structure and process control.